Laser powder bed fusion process parameters for the fabrication of unsupported overhang structures of metamaterial lattices - Wits, W.W.; Vos, C.J. de; Montero Sistiaga, M.L.; Smit, M.J. de (Elsevier, 2025)
Laser powder bed fusion of unsupported overhang structures, required for metamaterial lattices, are difficult to manufacture. In this study, process parameters are experimentally determined to successfully fabricate auxetic re-entrant metamaterial structures. Due to the support-less printing, higher linear energy densities compared to contour and hatch scanning are required to build continuously solidified overhang structures. Simulation results show that the melt pool width and in particular the length is enlarged, promoting loose powder attachment by denudation and balling. Auxetic re-entrant metamaterials are successfully fabricated. Impact tests show good mechanical performance and better energy absorption compared to previous studies.